Difficulty of isolating recalcitrant patients with infectious TB - Y. Nagata; T. Zama; S. Hirao; M. Urakawa; M. Ota (Public Health Action)
SETTING: Hospitals in Japan with more than five TB isolation beds. OBJECTIVES: Approximately 4,000 cases of sputum smear-positive TB were reported in 2022, who were isolated in a TB ward at least until they became sputum smear-negative. However, some recalcitrant patients are difficult to isolate because of their behaviour. This study aims to characterise recalcitrant patients with TB and determine why they left the hospitals. DESIGN: This was a descriptive study. We sent a self-administered questionnaire to the hospitals asking about recalcitrant inpatients with TB from April 2022 through March 2023. RESULTS: A total of 12 recalcitrant patients were identified, of whom 8 (66.7%) self-discharged, and the other 4 (33.3%) were discharged by the hospital. All were male with an average age of 58.9 years. The main reason why the patients were considered recalcitrant was related to psychiatric problems (41.7%), including 2 with possible dementia (16.7%). However, 3 (25.0%) patients verbally insulted or physically assaulted staff members and other patients. CONCLUSION: Although the number of recalcitrant patients was small, we recommend that there should be one or two TB facilities readily available for law enforcement officials to enforce isolation.